Tríade sombria da personalidade: conceitos, medição e correlatos - Monteiro, Renan Pereira (2017)
The present thesis aimed to explore the dark side of personality, verifying the fit of the measures that assess these traits, so as checking its relationships with diverse phenomena (e.g., emotional manipulation, impulsivity, values, infidelity, and tactics for mate attraction). For that, four articles were developed: one theoretical and three empirical. The first paper discusses the Dark Triad of personality, presenting this model that focuses on aversive personality traits that are part of a normal range of personality functioning. Ways were presented to measure these personality traits, highlighting, from an evolutionary perspective, the adaptive role that they can fulfil. The second paper (N = 243) aimed to adapt the two most used brief measures for the combined evaluation of the Dark Triad (Dirty Dozen and Short Dark Triad), providing evidences of validity (factorial and convergent) and internal consistency of these measures. In addition, analyses using the Item Response Theory made it possible to know the individual parameters of the items, specifically the difficulty and discrimination. This set of psychometric evidences was favorable to the Dirty Dozen, used in the further papers. The third paper (N = 397) evaluated the role of the Dark Triad, together with the Big Five and human values, for the prediction of attitudes and intentions to be unfaithful, with the last two explaining the engagement in extradyadic relationships. In general, the results showed that Machiavellianism, psychopathy and narcissism are individual differences that may predispose to infidelity. The fourth paper (N = 225) found that people with dark personality traits perform effective self-promotion mate attraction tactics for a short-term relationships, even controlling for the Big Five and sociosexual orientation, with psychopathy and narcissism being predictors of the use of such tactics for men, and only narcissism for women. The collected evidence highlight the important role of the Dark Triad of personality, and these traits facilitate the reproductive success of individuals, describing an impulsive profile, sensation seeker and able to manipulate others, being focused to casual relationships, betraying their partners when they are in committed relationships. Despite the fifteen years since the appearance of this personality model, it has been little discussed in Brazil. Thus, the present thesis contributes to the Brazilian literature providing psychometric evidences about measures that evaluate this group of traits, verifying the correlates to this set of factors that form the dark side of personality.